Hand hygiene during the spread of COVID-19: a cross-sectional study of awareness and practices among academic institutions in Lebanon - Alwan, Nisreen; Safwan, Jihan; Kerek, Racha; Ghach, Wissam (Frontiers in Public Health, 2024)
Introduction: During the pandemic, the World Health Organization has recommended hand hygiene as one of the effective preventive measures to limit the global spread of COVID-19. However, the awareness gap of hand hygiene protocols could increase the spread of COVID-19 and consequently increase the absenteeism rate among academic institutions. This study aims to assess hand hygiene awareness and practices levels among various university communities in Lebanon. Methods: A cross-sectional study was conducted between December 2021 and June 2022 among 1291 participants from academic settings in Lebanese universities. An online survey (score-based questionnaire) of hand hygiene was conducted to evaluate the awareness and practices among university communities (faculty, staff, and student). Mann-Whitney and Kruskal-Wallis tests were used to determine whether significant differences exist in the levels of awareness with regard to gender, age, provinces, educational level, and university status. Pearson’s chi-squared test was applied to assess differences among the sample characteristics and participants’ practice of hand hygiene. Results: It was found that most of the participants showed a moderate level of awareness (76.4%) with a mean score of 7.59 out of 12 (SD = 1.68). The Mann-Whitney test indicated that females recorded higher levels of awareness than males with a significant difference of p < 0.05. Another notable variable was the educational level of the participants with university degrees holders recording higher scores of awareness than the ones with high school degrees as per the Kruskal-Wallis test (p < 0.05). Significant differences were also shown in awareness scores among the age groups and the university status (p < 0.05). The Pearson’s chi-squared test results showed that females used alcohol-based hand rubs or soap and water more frequently than males (p < 0.05). However, males significantly preferred the frequent use of water alone compared to females (p < 0.05). Conclusions: The study findings highlighted the necessity of awareness campaigns and health educational programs addressing the technical skills of hand hygiene among both genders (especially males) of the academic communities in Lebanon.